The Role of Matrix Gla Protein in Ossification and Recovery of the Avian Growth Plate - Dan, Harel; Simsa-Maziel, Stav; Reich, Adi; Sela-Donenfeld, Dalit; Monsonego-Ornan, Efrat (Frontiers in Endocrinology, 2012)
Extracellular matrix mineralization is an essential physiologic process in bone, teeth, and hypertrophic cartilage. Matrix Gla protein (MGP), an inhibitor of mineralization, is expressed by chondrocytes and vascular smooth muscle cells to inhibit calcification of those soft tissues. Tibial dyschondroplasia (TD), a skeletal abnormality apparent as a plug of non-vascularized, non-mineralized, white opaque cartilage in the tibial growth plate of avian species can serve as a good model for studying process and genes involved in matrix mineralization and calcification. In this work, we studied the involvement of MGP in the development of TD, as well as in the processes of spontaneous and induced recovery from this syndrome. First, we found that during normal bone development, MGP is expressed in specific time and locations, starting from wide-spread expression in the yet un-ossified diaphysis during embryonic development, to specific expression in hypertrophic chondrocytes adjacent to the chondro-osseous junction and the secondary ossification center just prior to calcification. In addition, we show that MGP is not expressed in the impaired TD lesion, however when the lesion begins to heal, it strongly express MGP prior to its calcification. Moreover, we show that when calcification is inhibited, a gap is formed between the expression zones of MGP and BMP2 and that this gap is closed during the healing process. To conclude, we suggest that MGP, directly or through interaction with BMP2, plays a role as ossification regulator that acts prior to ossification, rather then simple inhibitor.